Hydrogen sulphide suppresses human atrial fibroblast proliferation and transformation to myofibroblasts - Sheng, Jingwei (Blackwell Publishing Ltd, 2013)
Cardiac fibroblasts are crucial in pathophysiology of the myocardium whereby their aberrant proliferation has significant impact on cardiac function. Hydrogen sulphide (H(2)S) is a gaseous modulator of potassium channels on cardiomyocytes and has been reported to attenuate cardiac fibrosis. Yet, the mechanism of H(2)S in modulating proliferation of cardiac fibroblasts remains poorly understood. We hypothesized that H(2)S inhibits proliferative response of atrial fibroblasts through modulation of potassium channels. Biophysical property of potassium channels in human atrial fibroblasts was examined by whole-cell patch clamp technique and their cellular proliferation in response to H(2)S was assessed by BrdU assay. Large conductance Ca(2+)-activated K(+) current (BK(Ca)), transient outward K(+) current (I(to)) and inwardly rectifying K(+) current (IK(ir)) were found in human atrial fibroblasts. Current density of BK(Ca) (IC(50) = 69.4 μM; n = 6), I(to) (IC(50) = 55.1 μM; n = 6) and IK(ir) (IC(50) = 78.9 μM; n = 6) was significantly decreased (P < 0.05) by acute exposure to NaHS (a H(2)S donor) in atrial fibroblasts. Furthermore, NaHS (100–500 μM) inhibited fibroblast proliferation induced by transforming growth factor-β1 (TGF-β1; 1 ng/ml), Ang II (100 nM) or 20% FBS. Pre-conditioning of fibroblasts with NaHS decreased basal expression of Kv4.3 (encode I(to)), but not KCa1.1 (encode BK(Ca)) and Kir2.1 (encode IK(ir)). Furthermore, H(2)S significantly attenuated TGF-β1–stimulated Kv4.3 and α-smooth muscle actin expression, which coincided with its inhibition of TGF-β–induced myofibroblast transformation. Our results show that H(2)S attenuates atrial fibroblast proliferation via suppression of K(+) channel activity and moderates their differentiation towards myofibroblasts.